Microplastics in zooplankton in the eastern Arabian Sea: The threats they pose to fish and corals favoured by coastal currents. (December 2021) - Rashid, C.P.; Jyothibabu, R.; Arunpandi, N.; Abhijith, V.T.; Josna, M.P.; Vidhya, V.; Gupta, G.V.M.; Ramanamurty, M.V.
Abstract: The baseline study of Microplastics (MPs) in zooplankton (copepods, chaetognaths, decapods, and fish larvae) from six different zones along India's west coast (off Kanyakumari/Cape Comorin, Kochi, Mangalore, Goa, Mumbai, and Okha) in the Eastern Arabian Sea (EAS) is presented here with their vast ecosystem impacts. This investigation revealed that zooplankton in all six zones accumulated MPs pellets (52.14%), fibres (28.40%), films (10.51%), and fragments (8.95%). The highest average retention of MPs (MPs/individual) was found in fish larvae (av. 0.57 ± 0.18) while copepods had the lowest (av. 0.03 ± 0.01). The presence of low-density polyethylene, polypropylene, polystyrene, and polyethylene terephthalate was confirmed by Raman Spectra of MPs. The MPs in zooplankton found in this study (av. 22 ± 7 pieces/m 3 ) were nearly 2-fold greater than those found in some of the world's most densely populated areas. It is shown that the strong southerly coastal currents could advect the MPs contaminated water mass too far away, having the potential to affect the fish and corals. Highlights: This pilot study on Microplastics (MPs) was focused on the west coast of India. MP contamination in selected marine zooplankton groups is being investigated. Out of four kinds of MPs found, the pellet type was the dominant one. MPs increased at higher trophic levels within the zooplankton community. High MPs in zooplankton and the coastal currents aggravate the risk of transferring them to fishes and corals.